Profil Fitokimia dan Penentuan Fenolik Total, Flavonoid Total, dan Uji Aktivitas Antioksidan Ekstrak Daun Sungkai (Peronema canescens Jack) dari Daerah Kota Padang - Adlis Santoni; Mai Efdi; Fadhillah, Nurul (Departemen Kimia Universitas Andalas, 2023)
Sungkai (Peronema canescens Jack) is a plant that is easy to find in Indonesia. Sungkai leaves are used by the community as herbal medicine to boost immunity. The purpose of this study was to determine the phytochemical profile, total phenolic content and total flavonoids and test the antioxidant activity of Sungkai leaf extract. Sungkai leaf extract was obtained by maceration method in stages. The results of the phytochemical screening showed that ethyl acetate extract and methanol extract contained phenolic and flavonoid compounds. Total phenolic test using the method Folin-Ciocalteu with the highest total phenolic content in methanol extract namely 172.75 mg GAE/g sample. Total flavonoid test using the AlCl3 method with the highest total flavonoid content in the ethyl acetate extract, namely 825.714 mg QE/g sample. Antioxidant activity test using the ABTS method with a very strong antioxidant activity in methanol extract with IC50 of 13.589 mg/L.